Konflik Sosial dalam Novel Kuda Karya Panji Sukma - Hidayat, Ahmad Taufik; Zulfadhli, Zulfadhli (Persona: Kajian Bahasa dan Sastra, 2024)
This research aims to analyze the forms of social conflict, their causes, and their consequences in the novel Kuda by Panji Sukma. Employing literary sociology as its theoretical framework, this qualitative study utilizes a descriptive approach. The novel Kuda serves as the primary data source. Data collection involved a meticulous reading of the novel, noting and cataloging instances of social conflict. The triangulation technique was used to ensure data validity. Data analysis was conducted by categorizing the utterances, actions, and thoughts of characters and the narrator in relation to the forms, causes, and effects of social conflict. The results were then analyzed, interpreted, and synthesized into a coherent narrative for the thesis. The findings reveal that the social conflicts in the novel can be classified into three main types: (1) interpersonal conflicts, (2) group conflicts, and (3) societal conflicts. The underlying causes of these conflicts were identified as: (a) individual differences, (b) conflicting interests, (c) social change, and (d) cultural disparities. Lastly, the study examined the consequences of social conflict, which were found to include: (a) increased group solidarity, (b) the breakdown of group unity, (c) the development of individual identity, (d) the erosion of social norms, and (e) property loss and casualties.